THE EFFECTIVENESS OF VOLUNTEERING IN THE FORMATION OF KNOWLEDGE ABOUT THE RIGHTS OF THE CHILD AMONG SCHOOLCHILDREN (World Bulletin of Social Sciences, 2023)
The given article is about effectiveness of volunteering in the formation of knowledge about the rights of the child among school learners. We have established cooperation with the Youth Union during our pilot work to improve the mechanisms for the protection of children's rights in secondary schools and to promote awareness of children's rights. During our research, we conducted experiments in cooperation with the Karakalpak branch of the Republican Children's Organization “Kamalak”, which operates within the Youth Union of Uzbekistan.
Keywords: children; providing children's rights; children's rights; tolerance